2012
DOI: 10.1007/s10570-012-9709-1
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent cellulose fibers activated by Eu3+-doped nanoparticles

Abstract: UV-active cellulose fibers were obtained by dry-wet method spinning an 8 % by weight acellulose solution in N-methylomorpholine-N-oxide (NMMO) modified by europium-doped gadolinium oxyfluoride Gd 4 O 3 F 6 :Eu 3? containing 5 mol (%) of the dopant. Photoluminescent nanoparticles were introduced in the in powder form into a polymer matrix during the process of cellulose dissolution in NMMO. The dependencies of emission intensity on excitation energy and the concentration of Gd 4 O 3-F 6 :Eu 3? nanoparticles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…High flexibility of the manufacturing process of cellulose fibres makes it possible to modify them by introducing into the spinning solution various chemically-different materials that allow obtaining functional fibres with specific properties. In this way cellulose fibres with, for example, electrically conductive and magnetic properties (Liu et al 2013), bioactive (Kulpinski et al 2011), sensor fibres (Rubacha 2007), and in recent years also these with luminescent properties were obtained (Kulpinski et al 2012a). On the basis of previous research it can be concluded that an additional advantage of this technology is the possibility to use modifiers with nanometric size of particles.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…High flexibility of the manufacturing process of cellulose fibres makes it possible to modify them by introducing into the spinning solution various chemically-different materials that allow obtaining functional fibres with specific properties. In this way cellulose fibres with, for example, electrically conductive and magnetic properties (Liu et al 2013), bioactive (Kulpinski et al 2011), sensor fibres (Rubacha 2007), and in recent years also these with luminescent properties were obtained (Kulpinski et al 2012a). On the basis of previous research it can be concluded that an additional advantage of this technology is the possibility to use modifiers with nanometric size of particles.…”
Section: Introductionmentioning
confidence: 97%
“…paper patching jacketed bullets, filters), and the space industry. The fibres containing in their structure specific chemical compounds with luminescent properties (Kulpinski et al 2012a) can be effective identifiers of both textile products, paper documents, and those made of plastic. They can also be helpful in management and control of production ) and transport and storage of products (not only the textile ones).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new generation of PAN fibers was elaborated (e.g. fibers with ceramic nanoparticles, such as silica, hydroxyapatite, montmorillonite or carbon nanotubes) [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the Department of Man-Made Fibers Technical University of Lodz, composite fibers with silver nanoparticles [8], magnetic or luminescent particles [9,10] or montmorillonite [11] have been obtained by introducing suitable additives into the bulk (by adding to spinning dope).…”
mentioning
confidence: 99%